A novel bioactive glass-based root canal sealer in endodontics - Gang Huang; Si-Yi Liu; Ji-Lin Wu; Dong Qiu; Yan-Mei Dong (Elsevier, 2022)
Background/purpose: Bioactive glass (BG), one type of bioceramics, shows similar or better characteristics to calcium silicate which has been regarded as a promising root filling material in endodontics. This study aimed to develop a novel BG-based root canal sealer for endodontics. Materials and methods: The novel BG-based root canal sealer was composed of phytic acid derived bioactive calcium phosphosilicate glass named PSC mixed with zirconium oxide (ZrO2) as powder, and phosphate solution (PS) dissolved with sodium alginate (SA) named PS-SA as liquid. Moreover, the physicochemical properties, mineralization, sealing ability and biocompatibility of the novel BG-based root canal sealer were evaluated. Results: This study developed a novel BG-based sealer named BGS-SA-Zr which contained the powder of PSC and ZrO2 and the liquid of PS-SA. Results indicated that the flow, film thickness and radiopacity of BGS-SA-Zr conformed to ISO 6876:2012. The setting time and solubility of BGS-SA-Zr were 53.7 ± 1.5 min and 21.46 ± 0.54%, respectively. The pH value of the simulated body fluid (SBF) immersed with BGS-SA-Zr raised slightly up to 7.70. The CCK-8 assay indicated that BGS-SA-Zr had no cytotoxic effects on MG-63 cells. After immersion in SBF for 4 weeks, dense hydroxyapatite crystals were observed on the surface of BGS-SA-Zr. Furthermore, there was no difference in the sealing ability between BGS-SA-Zr and the bioceramic sealer iRoot SP whether setting at 1 day or immersed in SBF for 4 weeks (P > 0.05). Conclusion: Our results suggest that the novel BG-based sealer may be a promising sealer for endodontic treatment.